1972
DOI: 10.1542/peds.49.5.671
|View full text |Cite
|
Sign up to set email alerts
|

The Small-for-Date Infant I. Later Growth Patterns

Abstract: In a prospective study, 96 of a possible 131 full term small-for-date (SFD) infants have been followed for a minimum of 4 years. Serial measurements for weight, height, and head circumference have been compared with the Stuart growth percentiles. By 4 years of age the mean weight and height were between the 10th and 25th percentiles with 35% below the 3rd and only 8% above the 50th percentiles. Increase in head circumference paralleled linear growth. Bone age showed a high positive correlation with height age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1975
1975
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In addition the percentage of infants with a length below the reference range for corrected gestational age at discharge is several times greater than at birth [1,2]. Various studies have indicated that the window for catch-up growth in growth-retarded babies is limited and that if such growth has not taken place in in-fancy, the chances that it will occur later diminish [3][4][5]. In humans, the importance of nutrition in early life is now well known, and the term "programming" has been proposed to emphasise that early nutrition should be considered not simply in terms of providing immediate nutritional needs but also because of certain biological effects that may have lasting or lifelong significance [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition the percentage of infants with a length below the reference range for corrected gestational age at discharge is several times greater than at birth [1,2]. Various studies have indicated that the window for catch-up growth in growth-retarded babies is limited and that if such growth has not taken place in in-fancy, the chances that it will occur later diminish [3][4][5]. In humans, the importance of nutrition in early life is now well known, and the term "programming" has been proposed to emphasise that early nutrition should be considered not simply in terms of providing immediate nutritional needs but also because of certain biological effects that may have lasting or lifelong significance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps longer follow-up periods will document this in other study populations as well. Both term and preterm infants who are small for gestational age have less capacity for catch-up growth (101,113,114). Dysmaturity may not alter the capacity for catch-up growth (115).…”
Section: Growth Of Low Birth Weight Infantsmentioning
confidence: 99%
“…On the other hand, persistently small head circumference may be associated with neurologic dysfunction (100,104). Head circumference growth generally parallels linear growth (112,113,116) and disproportionately rapid "catch-up" or slow head growth should be a cause for concern.…”
Section: Growth Of Low Birth Weight Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal hypertension is the most common cause of intrauterine growth retardation. There have been many studies of long‐term follow‐up of small for gestational age babies 1–6 . These are often a heterogenous group, even if babies with major congenital malformations, chromosomal abnormalities or congenital viral infections are excluded.…”
mentioning
confidence: 99%